Editorial for the Special Issue on Micromachines for Non-Newtonian Microfluidics - Lanju Mei; Shizhi Qian (Micromachines, 2022)
Microfluidics has seen a remarkable growth over the past few decades, with its extensive applications in engineering, medicine, biology, chemistry, etc [...]